Referential Cohesion in Donald Trump`s Speech Transcript - Agus Wirawan, I Wayan Gede (Humanis; Vol 22 No 2 (2018), 2018)
Cohesion establishes the text or sentences and gives their meaning by the grammatical and lexical linking.   Halliday and Hasan (1976) In Cohesion in English, identify five general categories of cohesive devices that are possibly implemented in texts: reference, ellipsis, substitution, lexical cohesion and conjunction. One of the cohesion meanings is reference. Reference is one of cohesive devices, and it contains the specific nature of the information needed to be retrieved for the comprehensive information. The problems discussed in this study are the type of reference applied in the speech transcripts and referential meaning presented in the speech transcripts of Donald Trump`s Speech. The aims of the study were to find out the reference applied in the speech transcripts and referential meaning of the reference  presented in the speech transcripts. The main theory used was Theory of Cohesion proposed by Halliday and Hasan (1976). The data in this study were taken from the website of Washington Post in form of transcripts. The data were collected using observation method and analyzed using qualitative method. There were two kinds of reference found in the speech; which were personal reference and demonstrative reference. The personal reference that occurred in the speech transcript included   I, you, we, he, she, they, and it. Meanwhile, the demonstrative references that appeared in the speech transcript were this, these, there, here, now and the. These references were presented as endophoric, whether anaphoric or cataphoric. The comparative reference was absent. From this study, it can be concluded that referential cohesion takes an important role in a text or in this case speech transcripts, since the function of reference is to hold a text together and give its meaning.